2012
DOI: 10.1093/nar/gks144
|View full text |Cite
|
Sign up to set email alerts
|

Widespread occurrence of 5-methylcytosine in human coding and non-coding RNA

Abstract: The modified base 5-methylcytosine (m5C) is well studied in DNA, but investigations of its prevalence in cellular RNA have been largely confined to tRNA and rRNA. In animals, the two m5C methyltransferases NSUN2 and TRDMT1 are known to modify specific tRNAs and have roles in the control of cell growth and differentiation. To map modified cytosine sites across a human transcriptome, we coupled bisulfite conversion of cellular RNA with next-generation sequencing. We confirmed 21 of the 28 previously known m5C si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
940
5
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 840 publications
(992 citation statements)
references
References 57 publications
42
940
5
5
Order By: Relevance
“…In coding mRNAs, we found that the identified modifications included previously characterized adenosine methylation (m 1 A) and Y sites (Squires et al, 2012;Carlile et al, 2014;Schwartz et al, 2014b), as well as novel cytosine (m 3 C) and guanosine methylation (m 1 G), dihydrouridylation (D), N 6 -isopentenyladenosylation (i 6 A), and threonylcarbamoyladenosylation (t 6 A) ( Figure 4B; Supplemental Figure 6). As in noncoding RNAs, the distribution of these modification types is distinct between stable RNA, smRNA, and uncapped, degrading transcripts.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…In coding mRNAs, we found that the identified modifications included previously characterized adenosine methylation (m 1 A) and Y sites (Squires et al, 2012;Carlile et al, 2014;Schwartz et al, 2014b), as well as novel cytosine (m 3 C) and guanosine methylation (m 1 G), dihydrouridylation (D), N 6 -isopentenyladenosylation (i 6 A), and threonylcarbamoyladenosylation (t 6 A) ( Figure 4B; Supplemental Figure 6). As in noncoding RNAs, the distribution of these modification types is distinct between stable RNA, smRNA, and uncapped, degrading transcripts.…”
mentioning
confidence: 87%
“…While modifications are best characterized in noncoding tRNAs and rRNAs, mRNAs have also been found to contain N 6 -methyladenosine (m 6 A) (Horowitz et al, 1984;Dominissini et al, 2012;Meyer et al, 2012), 5-methylcytosine (m 5 C) (Squires et al, 2012), inosine (I) (Li et al, 2009;Wulff et al, 2011), and pseudouridine (Y) (Carlile et al, 2014;Schwartz et al, 2014b). Additionally, there is a growing body of evidence to support the functional significance of RNA modifications within mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…3 Mapping of m 5 C in RNA was initially attempted by adapting the bisulfite sequencing technology used for m 5 C in DNA, leading to the identification of approximately 10,000 m 5 C sites in mRNA. 26,27 Subsequently, new methods were developed that leverage m 5 C methyltransferases to enrich m 5 C-containing RNA, either by incorporating 5-azacytidine into RNA, 28 or by mutating the methyltransferase 29 to enable modified RNA capture. These methods identified far fewer m 5 C sites in mRNA, on the order of a few hundred to one thousand, respectively.…”
Section: Mrnamentioning
confidence: 99%
“…While its biological function remains unclear, some of the machinery that regulates m 5 C in different RNA classes has been identified: Trm4p (in yeast), 31 and DNMT2 and NSUN2 (in human) have been identified as m 5 C methyltransferases. 27,32 While the roles and specificities of these enzymes is controversial, their functional characterization will likely aid in uncovering the roles of m 5 C in the future. [33][34][35] For instance, a recent study suggested functional roles for m 5 C oxidation to 5-hydroxymethylcytidine in D. melanogaster mRNA.…”
Section: Mrnamentioning
confidence: 99%
“…Please do not adjust margins Please do not adjust margins 176 and RNA. 177 It is an important regulator of gene expression in eukaryotes and a guardian against methylation-sensitive endonucleases in prokaryotes.…”
Section: Bisulfite Sequencing For M 5 Cmentioning
confidence: 99%